2007
DOI: 10.1007/s10562-007-9141-6
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectra and dissociation of aqueous Na2SiO3 solutions

Abstract: To facilitate molecular spectroscopic observation of the mysterious transition of dissolved sodium silicate molecules into nanoparticles of desired silica gel and zeolite structures, the IR and Raman spectra of Na 2 H 2 SiO 4 monomers are studied here in details. It is demonstrated that the 3-0.2 mol/L aqueous solutions of Na 2 SiO 3 and Na 2 SiO 3 Â 9H 2 O contain mostly Na 2 H 2 SiO 4 monomers dissociated about 30%-80%, respectively. In contrast to the common belief the Si-O vibrations of these monomers depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 83 publications
2
46
0
Order By: Relevance
“…In general the low frequency band can be assigned to the symmetric and the two high frequency bands to asymmetric [Si-O] stretches of the different silica species and structures in the sodium silicate solutions. The position and intensities of these bands have previously been shown to depend on both concentration and/or SiO 2 :Na 2 O ratio in the solutions, reflecting changes in structure and speciation [25][26][27].…”
Section: Si Nmrmentioning
confidence: 94%
“…In general the low frequency band can be assigned to the symmetric and the two high frequency bands to asymmetric [Si-O] stretches of the different silica species and structures in the sodium silicate solutions. The position and intensities of these bands have previously been shown to depend on both concentration and/or SiO 2 :Na 2 O ratio in the solutions, reflecting changes in structure and speciation [25][26][27].…”
Section: Si Nmrmentioning
confidence: 94%
“…Although there are a number of studies on the assignments of vibration bands of silica solids, glasses and gels [31,32], the assignments related to the distribution of anionic species in sodium silicate solution, especially very dilute solutions, are still unclear and some even incompatible [16][17][18]. To obtain the distribution of silicate species with pH and concentration, a silicate speciation model was set up using WinSGW program [33].…”
Section: Spectra Of Aqueous Sodium Silicatementioning
confidence: 99%
“…Halasz et al reported infrared spectra of sodium silicate solutions dissolved from Na 2 SiO 3 and Na 2 SiO 3 ·9H 2 O at pH >13 [18].…”
Section: Spectra Of Aqueous Sodium Silicatementioning
confidence: 99%
See 1 more Smart Citation
“…Thus FTIR and Raman spectroscopic methods are very efficient for studying kinetic processes and precursor clusters as well as to identify small-sized crystalline particles in the final product. 10,13,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] In addition, FTIR and Raman spectroscopy are very sensitive to atomic bonding and thus gives the opportunity to study active sides and interactions between embedded functional molecules and framework atoms in porous materials. 5,12,[33][34][35][36][37][38][39][40][41][42] Raman spectroscopy compares favourably to FTIR spectroscopy because of the better signal-to-noise ratio in the low-energy spectral range and the better spatial resolution when a microscope is used.…”
Section: Introductionmentioning
confidence: 99%